x -y = 3
x/3 + y/2 = 6
Answers
Answered by
9
... Heya your answer is here...
Attachments:
![](https://hi-static.z-dn.net/files/da8/3c7ae4159dabc8f9a3aed3350eaf9b10.jpg)
vishal27102003:
thank yoy Anjali
Answered by
4
HI DEARS
X-Y = 3.......[1]
x/3 + y/2 = 6
BY L.C.M ==> 2X+3Y/6 = 6
==> 2X+3Y = 36........[2]
FROM eq[2] by eq[1]
x-y = 3
2x+3y = 36
multiply eq[1] by 2
2x-2y = 6
2x+3y = 36
==> -5x = -30
==> x = 30/5
==> x = 6
NOW PUT THE VALUE OF X IN eq[1]
2X-2Y = 6
2[6] - 2Y = 6
12-2Y = 6
-2Y = -6
Y = 3
I HOPE ITS HELPFUL
Similar questions